PTH-136 Gender Differences in Leadership, Workforce, and Scholarly Presentation within A National Society; A Gastroenterology Perspective. (17th August 2016) - Brooks, AJ; Arthurs, EA; Edwards, C; Gardner, R; Lockett, MJ; Neild, P; Solomon, J; Taylor, EJ; Thomas-Gibson, S; Eaden, J; ,
Abstract : Introduction: In the UK, gastroenterology historically has been a male predominant medical speciality, but specific data regarding the outcomes of gender within workforce, academia and leadership at a national level are lacking. Methods: Data regarding scholarly presentation at the British Society of Gastroenterology (BSG) 2013, 2014, 2015 annual conferences were collected and analysed. In 2015 this included member societies for Digestive Diseases Federation (DDF). Data from the 2013–2015 BSG annual workforce report were examined. Results: In 2015 female higher speciality trainees made up 39% (328/850) of the trainee workforce, compared to 37% and 35% in 2014 and 2013 respectively. From 2013–2015 the proportion of female academic trainees has been 22%, 23% and 24% respectively. In the years from 2013–2015, less than a fifth (18%) of all consultant gastroenterologists were female. Female consultant (18%), trainee (39%), associate (86%) and student attendance (47%) at DDF 2015 did not change significantly from 2013–2014. The number of female speakers 43/331 (13%) was significantly lower at DDF 2015 compared with BSG 2014 56/212 (26.4%) ( P = 0.0001) and BSG 2013 63/231 (37%) ( P = 0.0001). The number of female chairs did not differ between the annual conferences; 23/173 (13%) in 2015, 20/94 (21%) in 2014, 29/118 (25%) in 2013, nor did delivery of the named lectures; 2/15 (13%) in 2015, and 1/6 (17%) in both 2014 and 2013. Prizes (oral, poster, 'Dragon's Den) awarded to females was 44%, 30% and 20% respectively, and did not differ significantly in 2013/2014. Female leadership at the BSG via representation at Council and Executive was 4/30 (13%) in 2015, and did not differ in 2013/2014, with no elected council members since 2008 and 1 female president in 1973. Conclusion: The proportion of female gastroenterology trainees and consultants is increasing, but remains lower than across all medical specialties at 52% and 34% respectively. 1 Female attendance and scholarly presentation at conferences reflects the workforce. Lower numbers of female speakers at DDF 2015 may reflect differences in surgical and allied specialties. Action within the BSG is underway to address female underrepresentation in leadership roles. Strategies to encourage female recruitment and retention to gastroenterology are being tested and evaluated. Reference: 1 Census of consultant physicians and higher speciality trainees in the UK, 2014–2015. RCP, 2016. Disclosure of Interest: None Declared